2013
DOI: 10.1016/j.jcmg.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography in Liver Transplant Candidates

Abstract: Involvement of the cardiovascular system in patients with end-stage liver disease (ESLD) is well recognized and may be seen in several scenarios in adult liver transplantation (LT) candidates. The hemodynamic effects of ESLD may result in apparent heart disease, or in some instances may mask cardiac disease. Alternatively, cardiac disease can occasionally be the underlying etiology of ESLD. LT imposes significant hemodynamic stresses, with cardiovascular complications accounting for considerable perioperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 66 publications
1
59
0
2
Order By: Relevance
“…In contrast to the Hepatorenal Syndrome and renal insufficiency [36], it is not fully clear how coronary heart disease is linked to end-stage liver disease [37] but these patients clearly have an increased risk of mortality [38] independently of liver transplantation. While some literature sources have suggested that a protective effect of cirrhosis on atherosclerosis and myocardial infarction might exist [39], [40], there is a prevalence of coronary heart disease of up to 27% in patients with end-stage liver disease [35], [41][43].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the Hepatorenal Syndrome and renal insufficiency [36], it is not fully clear how coronary heart disease is linked to end-stage liver disease [37] but these patients clearly have an increased risk of mortality [38] independently of liver transplantation. While some literature sources have suggested that a protective effect of cirrhosis on atherosclerosis and myocardial infarction might exist [39], [40], there is a prevalence of coronary heart disease of up to 27% in patients with end-stage liver disease [35], [41][43].…”
Section: Discussionmentioning
confidence: 99%
“…The peripheral vasodilation and elevated cardiac output of ESLD result in high transvalvular flows velocities that may overestimate the degree of stenosis [13, 14]. Cirrhotic cardiomyopathy will mask left ventricular systolic dysfunction and induce diastolic dysfunction and left ventricular hypertrophy [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…The careful use of dobutamine stress echocardiography, as well as transesophageal echocardiography and catheter-based assessments, may help to verify the severity of AS and distinguish entities such as pseudo AS and paradoxical low-flow, low-gradient AS [1820]. The use of a gradient only based assessment of valve severity should be discouraged [14]. …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other surgical stresses including TIPS have also been reported to be accompanied by an increase in the pulmonary capillary wedge pressure and to precipitate overt heart failure in these patients [28]. Unfortunately, predicting patients who are more prone to the development of post-transplantation/ TIPS cardiac complications is still a big challenge [1,29]. Two-dimensional and dobutamine stress echocardiography were utilized to predict the development of adverse cardiac events following liver transplantation and both had a low predictive value [27].…”
Section: Post-interventional Cardiac Complications Can We Add Somethmentioning
confidence: 99%